BAS/BSCR43 X-box binding protein 1 splicing is crucial in endothelial cell proliferation. Issue 17 (26th August 2010) - Zeng, Lingfang; Xiao, Qingzhong; Li, Hongling; Margariti, Andriana; Hu, Yanhua; Xu, Qingbo
Abstract : The X-box binding protein 1 (XBP1) is an endoplasmic reticulum stress response transcription factor. Our previous study showed that sustained activation of XBP1 splicing led to atherosclerosis development (Zeng et al. PNAS 2009). However, the function of XBP1 expression and splicing in endothelial cells and angiogenesis remains unclear. To study this issue, we generated XBP1 knockout mice by deletion of exons 1 and 2 of the gene. XBP1-null (XBP1−/−) embryos at E12.5 showed growth retardation and pale colouration phenotype. The average body weight of XBP1−/−embryos was 40% less than that of wild-type (XBP1+/+) animals. The blood vessel density in XBP1−/− embryos was significantly reduced, owing to a smaller number of CD31+ and Flk1+ cells. In in vitro culture of whole embryonic cells, XBP1−/− cells grew significantly more slowly and lost response to VEGF stimulation. To study the mechanism of XBP1-mediated cell growth, human umbilical vein endothelial cells were treated with VEGF that transiently activated IRE1α phosphorylation at Ser724. The mRNA movement inhibitor, cycloheximide, ablated VEGF-induced IRE1α phosphorylation and XBP1 splicing. Co-immunoprecipitation assay showed that there was interaction among KDR, IRE1α and unspliced XBP1 (XBP1u), which could be increased by VEGF treatment. Further experiments demonstrated that the C-terminal region of KDR and the kinase domain of IRE1α are responsible for their interactions. MTT and BrdU incorporation assays indicate that transient activation of XBP1 splicing increased while long-term activation decreased endothelial survival and proliferation. Knockdown of XBP1 or IRE1α ablated VEGF-induced proliferation in endothelial cells. Immunofluorescent staining and TOP Flash reporter assay showed that overexpression of XBP1s increased β-catenin translocation into the nucleus. Thus, this study demonstrated for the first time that XBP1 is crucial for endothelial growth and angiogenesis, in which VEGF-stimulated IRE1α/XBP1 splicing system and interaction with β-catenin are key elements, indicating a potential target of XBP1 for protecting endothelial integrity.